Antiplasmodial activities of gold(I) complexes involving functionalized N-heterocyclic carbenes. Issue 13 (1st July 2016) - Hemmert, Catherine; Ramadani, Arba Pramundita; Boselli, Luca; Fernández Álvarez, Álvaro; Paloque, Lucie; Augereau, Jean-Michel; Gornitzka, Heinz; Benoit-Vical, Françoise
Graphical abstract: Abstract: A series of twenty five molecules, including imidazolium salts functionalized by N-, O- or S-containing groups and their corresponding cationic, neutral or anionic gold(I) complexes were evaluated on Plasmodium falciparum in vitro and then on Vero cells to determine their selectivity. Among them, eight new compounds were synthesized and fully characterized by spectroscopic methods. The X-ray structures of three gold(I) complexes are presented. Except one complex (18 ), all the cationic gold(I) complexes show potent antiplasmodial activity with IC50 in the micro- and submicromolar range, correlated with their lipophilicity. Structure–activity relationships enable to evidence a lead-complex (21 ) displaying a good activity (IC50 = 210 nM) close to the value obtained with chloroquine (IC50 = 514 nM) and a weak cytotoxicity.